Maximizing Productivity of Cucumber (Cucumis sativa L) Applied with Bio-Stimulant Solution - Oñal, Jr., Paulino A; Lapas, Patricia S.; Servino, Rizzi Ann S.; Andrade, Francis E.; Cortez, Manuel D.; Baldonebro, Jessel Jane G. (Future Science / FSH-PH Publications, 2024)
The study sought to determine the effects of different levels of concentrations of bio-stimulant solution (BSS) in enhancing the growth and maximizing the yield of the cucumber plant. The study was conducted at UNO-R School of Agriculture, Philippines, last January 8, 2024, to March 18, 2024. The study was laid out in (CRD) with four treatments and replicated 4 times. The BSS solution was diluted in the water. It was applied at the base of the vine following the research protocol. Statistical analysis revealed highly significant differences among the treatments in growth and yield parameters such as length of vine and weight of marketable fruits, respectively. Likewise, results showed highly significant differences among treatments on flower initiation, number of leaves, number of fruits, circumference, and diameter of fruits, biomass, and root weight. For the longest vine, greater number of leaves, early flower initiation, great number of fruits, greater length and bigger circumference of fruits, heavier weight of fruits, heavier roots, and biomass accumulation were obtained from plants applied with 400ml BSS, followed by 300ml BSS, and 200ml BSS, respectively. While those who have no BSS had the lowest result in almost all of the parameters mentioned above. Four growth characteristics are strongly correlated with the length of vines, and three for the root weight, respectively. This study recommends the use of 400ml BSS in enhancing the growth and maximizing the yield of cucumber.